The Role of vaccination in reducing Covid-19 anxiety : Peran vaksinasi dalam menurunkan kecemasan Covid-19 - Eka Apristian Pantu; Anisawati Talawo; Ucok Senggi; Nabilah Kartika Mamonto (Talenta Publisher, 2023)
One of the programs taken to deal with the Covid-19 pandemic is the implementation of vaccination. This study aims to explain the relationship between vaccination and COVID-19 anxiety. The subjects in this study were 259 students from the State Islamic Institute of Sultan Amai Gorontalo. The instrument used in this study was the fear of coronavirus-19 scale from Ahorsu et al. and analyzed using the Pearson correlation technique. The results showed a significant relationship between vaccination and anxiety about contracting COVID-19. This research is expected to be able to enrich the literature regarding anxiety about contracting Covid-19.